Analysis of ecological literacy level and creative thinking skills of college students - Diana Vivanti Sigit; Rizhal Hendi Ristanto; Ratna Komala; Anisa Nurrismawati; Puji Prastowo; Abubakar Sidik Katili (Institute of Advanced Engineering and Science, 2024)
Higher education institution is one of educational institutions that serve as a place of cultural values, and norms expected to become a foundation to foster caring attitudes toward the environment. These attitudes are accordingly meant to develop ecological literacy in order to overcome environmental problems which are likely to be minimized by combining ecological literacy and creative thinking skills. A quantitative descriptive with correlational study was employed in this research. There were 275 college students from three areas in Indonesia, namely Jakarta, Sumatera, and Gorontalo involved as respondents of the research. Data was collected by means of Google Forms consisting of tests and opinions. The ecological literacy was analyzed using dimensions of caring, practical competence, and knowledge while the creative thinking skills were analyzed using dimensions of fluency, originality, flexibility, and elaboration. This research is limited to students in the Department of Science and Non-Science. Findings of the research indicates that the ecological literacy level is in the medium category, whereas the creative thinking skills are good. Female students have a higher average score in ecological literacy and creative thinking skills compared to that of male students. Thus, there is a positive relationship between ecological literacy and creative thinking skills.